2023
DOI: 10.1111/jdi.14066
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemoglobin glycation index and non‐alcoholic fatty liver disease in the patients with type 2 diabetes mellitus

Abstract: Aims/IntroductionThe hemoglobin glycation index (HGI) represent the disparity between actual glycated hemoglobin measurements and predicted HbA1c. It serves as a proxy for the degree of non‐enzymatic glycation of hemoglobin, which has been found to be positively correlated with diabetic comorbidities. In this study, we investigated the relationship between HGI and non‐alcoholic fatty liver disease (NAFLD), along with other relevant biological markers in patients with diabetes.Materials and MethodsThis cross‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Several previous investigations have shown that HGI is strongly associated with adverse cardiovascular events [ 18 ], kidney injury [ 24 , 25 ], and nonalcoholic fatty liver disease [ 26 ]. However, both high HGI and low HGI appear to be associated with poor prognosis to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous investigations have shown that HGI is strongly associated with adverse cardiovascular events [ 18 ], kidney injury [ 24 , 25 ], and nonalcoholic fatty liver disease [ 26 ]. However, both high HGI and low HGI appear to be associated with poor prognosis to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of this variability on cardiovascular disease and mortality remains controversial (20). Several previous studies have shown that HGI is strongly associated with adverse cardiovascular events (21), kidney injury (22) and NAFLD (23). Some studies suggest that both high HGI and low HGI seem to be associated with poor prognosis to varying degrees.…”
Section: Discussionmentioning
confidence: 99%